2019
DOI: 10.3390/pathogens8040164
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Carbapenem-Resistant Escherichia fergusonii Strains Harbouring Beta-Lactamase Genes from Clinical Samples

Abstract: Recently discovered extraintestinal Escherichia fergusonii obtained from non-clinical samples has exhibited the potential for acquiring multiple beta-lactamase genes, just like many extraintestinal Escherichia coli strains. Albeit, they are often omitted or classified as E. coli. This study aimed to, therefore, identify carbapenem-resistant extended-spectrum beta-lactamase (ESBL) producing E. fergusonii isolates from clinical samples, determine their evolutionary relatedness using 16S rRNA sequencing analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
5
16
0
Order By: Relevance
“…In this study, E. fergusonii was identified by phenotypic methods as E. coli. However, by molecular techniques, a more precise identification was achieved, coinciding with previous publications that clarified the need to correctly identify this species to complete a taxonomic assignment and accurate epidemiological report (10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In this study, E. fergusonii was identified by phenotypic methods as E. coli. However, by molecular techniques, a more precise identification was achieved, coinciding with previous publications that clarified the need to correctly identify this species to complete a taxonomic assignment and accurate epidemiological report (10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 70%
“…With the use of phenotypic methods, E. fergusonii is usually identified as E. coli (12,13). Epidemiologically, bacterial misclassification leads to underreporting pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adesina et al, identified Escherichia fergusonii in septic wound samples obtained from patients at a general hospital in Lagos, Nigeria [ 6 ]. E. fergusonii is often identified as Escherichia coli or Shigella sp.…”
mentioning
confidence: 99%